The Practice of Kau Cim - Mumbai Archive Project Team (Jio Institute, 2024)
Fortune Sticks, known as Kau Cim, are bamboo sticks inscribed with numbers. These sticks are shaken out of a container to reveal fortunes, with each number corresponding to a written fortune that can be interpreted by temple staff. Kau Cim is often performed in temples dedicated to popular deities such as Guanyin (Goddess of Mercy), Guan Yu (God of War), and Mazu (Goddess of the Sea).